ANALISIS IMPLEMENTASI MODEL PEMBELAJARAN INOVATIF DAN TANTANGAN PEDAGOGIS GURU DALAM PEMBELAJARAN BIOLOGI SISTEM INDERA DI SMA NEGERI 2 BALIGE - Siburian, Roulina; Chyntia Dwi Camelia; Nurul Ummi Lubis; Rahel Octavia Siahaan; Widya Arwita; Rizal Mukra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the implementation of innovative learning models and the pedagogical challenges faced by teachers in teaching the sensory system in biology at SMA Negeri 2 Balige. The research is motivated by the need to improve the quality of biology learning, which is often still teacher-centered and less effective in fostering students’ critical thinking skills. The objective of this study is to analyze how innovative learning models are applied and to identify the pedagogical challenges encountered by teachers during the learning process. This research employed a descriptive qualitative approach involving one biology teacher and 36 tenth-grade students. Data were collected through in-depth interviews and analyzed descriptively to provide a comprehensive understanding of classroom practices. The findings indicate that innovative learning models such as Problem-Based Learning (PBL), Inquiry Learning, and Blended Learning have been implemented systematically and have contributed to a shift toward student-centered learning. The use of various instructional media, including PowerPoint, videos, animations, and anatomical models, supports students’ conceptual understanding. However, several challenges were identified, including differences in students’ abilities, limited instructional time, and constraints in developing innovative media. This study highlights the importance of integrating learning models and media effectively, supported by strong pedagogical competence. The findings provide practical implications for improving biology teaching quality through innovative and adaptive instructional strategies.